Crises of Power and Social Unrest in the People’s Republic of Poland and State Housing Policy - Kujawa, Jakub (Studia Historiae Oeconomicae, 2025)
The article examines the impact of socio-economic crises during the communist era on the functioning of the housing system between 1956 and 1989. It analyses several key issues, such as the effects of changes in governance on housing policy implementation, the extent and influence of social protests on this policy, and the significance of housing for the leadership of the Polish United Workers' Party (PZPR) during and after the crisis. The study's conclusions are diverse. First, shifts in government leadership led to adjustments in housing strategy. The most significant reforms in housing policy occurred in the late 1950s and the early 1970s. However, these changes did not alter the core of housing policy, which remained centralized until the end of the Polish People's Republic. Second, the ruling communists often used housing issues for their own gain, usually approaching them instrumentally. Third, housing was never a source of serious conflict or division within the Polish United Workers' Party (PZPR). Fourth, housing was not the main cause of conflict between society and authorities; social protests primarily targeted economic policies like pricing and wages. Nevertheless, housing demands appeared in strikes and protests. This ongoing issue, coupled with ineffective state reforms, made housing a factor contributing to conflict and increased the risk of social unrest against the authorities of the Polish People's Republic. Fifth, during periods of socio-economic crisis, social groups also attempted to develop their own solutions to prevent housing construction collapse. This was evident at the start and end of the 1980s, when Solidarity was active. However, the corrective plans they proposed were not implemented during the communist era, and after 1989, their potential largely remained unexploited.